Outcome Assessment and Impact Estimation: FTA Research Contributions Addressing Accelerating Rates of Deforestation and Forest Degradation (Challenge 1) - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The study “Outcome Assessment and Impact Estimation: FTA’s Research Contributions Addressing Accelerating Rates of Deforestation and Forest Degradation (Challenge 1)” is part of a series of integrative studies that aim to assess the extent to which the Forests, Trees and Agroforestry (FTA) CGIAR Research Program (CRP) has contributed to solutions that address key global challenges since the program’s inception in 2011. This report was prepared by FTA Monitoring, Evaluation, Learning and Impact Assessment (MELIA) specialists in CIFOR-ICRAF, Bioversity International, FTA, and in close collaboration with the Sustainability Research Effectiveness (SRE) team at Royal Roads University.